2014
DOI: 10.1002/hyp.10278
|View full text |Cite
|
Sign up to set email alerts
|

Flood frequency under the influence of trends in the Pearl River basin, China: changing patterns, causes and implications

Abstract: Using a nonstationary flood frequency model, this study investigates the impact of trends on the estimation of flood frequencies and flood magnification factors. Analysis of annual peak streamflow data from 28 hydrological stations across the Pearl River basin, China, shows that: (1) northeast parts of the West and the North River basins are dominated by increasing annual peak streamflow, whereas decreasing trends of annual peak streamflow are prevailing in other regions of the Pearl River basin; (2) trends si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 38 publications
1
11
1
Order By: Relevance
“…Therefore, the TC-induced rainstorms can easily The flood event was defined as the annual maximum daily discharge which is consistent with previous studies (e.g. Zhang et al, 2015aZhang et al, , 2015bVillarini et al, 2011a). The annual maximum daily discharge with unit of m 3 /s was used as the flood peak series.…”
Section: Study Region and Datasupporting
confidence: 72%
“…Therefore, the TC-induced rainstorms can easily The flood event was defined as the annual maximum daily discharge which is consistent with previous studies (e.g. Zhang et al, 2015aZhang et al, , 2015bVillarini et al, 2011a). The annual maximum daily discharge with unit of m 3 /s was used as the flood peak series.…”
Section: Study Region and Datasupporting
confidence: 72%
“…Clarke (2007) indicated that the next few decades should witness a substantial increase in our understanding of the processes causing climate change, not only for the purpose of forecasting the development of such changes, but also for predicting the frequency of an event of a certain magnitude. Thus, a number of investigators have attempted to incorporate nonstationarity in flood frequency analysis (Silva et al, 2012;Zhang et al, 2014bZhang et al, , 2015b. Reports on occurrence rates of floods in arid regions with the consideration of nonstationarity are lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Zheng et al, [7] indicated that annual and seasonal rainfall show no significant changes in the Pearl River Basin. Zhang et al, [75] indicated that uneven distribution of precipitation occurs in the flood and drought stages of the basin. Wu et al, [76] indicated that extreme precipitation has a significant increase in the Tarim River Basin.…”
Section: Variation Analysis Of Conventional Precipitation and Extremementioning
confidence: 99%